Pseudohypotension in the operating theatre ‐ a false alarm due to subclavian artery stenosis. Issue 2 (12th July 2016) - Pillay, Nanthini; Quek, KH
Summary: We present a case of pseudohypotension in a patient with undiagnosed left subclavian artery stenosis who underwent emergency surgery. The patient was misdiagnosed as being hypotensive intra‐operatively because the blood pressure was measured non‐invasively on the affected arm. He was thought to have local anaesthetic systemic toxicity and subjected to the inconvenience, cost and possible adverse effects of inappropriate treatment. This case highlights the fact that vascular surgical patients may have subclavian artery stenosis which is usually asymptomatic. Pseudohypotension can be avoided if blood pressure is measured in both arms in patients with peripheral vascular disease.